Chinese Herbal Medicine for Myasthenia Gravis: A Systematic Review and Meta-Analysis - Chen, Shuang; Xu, Meng-Bei; Zhou, Xiao-Li; Rong, Pei-Qing; Jin, Ting-Yu; Zheng, Guo-Qing (Frontiers in Pharmacology, 2018)
Myasthenia gravis (MG) is an acquired autoimmune disease with the disorder of the neuromuscular junction transmission caused by autoantibodies.Currently, various Chinese herbal medicines (CHMs) are widely used for MG. This meta-analysis was conducted to assess the effectiveness and safety of CHMs for MG and its possible mechanisms. Fourteen studies with 1039 individuals were identified by searching 7 databases from inception to March 2017.The methodological quality was assessed by using 7-item criteria from the Cochrane’s Collaboration tool, andwhich assessed ≥4 “yes” in the domains were selected for detailed assessment and meta-analysis. All the data were analyzed using Rev-Man 5.3 software. Meta-analysis showed a significant effect of CHMas adjuvant therapy for improving the effectiveness compared with WCM alone or placebo in treating myasthenia gravis (P<0.01). Moreover, there were fewer adverse effects and relapse rate in total when compared with control group. The possible mechanisms of CHM for MG are associated with immunoregulation by reconstituting of functional ability of Tregs. In conclusion, despite the apparent positive results, the present evidence supports, to a extent, that CHM can be used for MG patients because the methodological flaws and CHM heterogeneity. Further rigorous RCT for MG is needed.